2014
DOI: 10.1016/j.jgr.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng total saponin modulates the changes of α-actinin-4 in podocytes induced by diabetic conditions

Abstract: BackgroundThe actin cytoskeleton in podocytes is essential for the maintenance of its normal structure and function. Its disruption is a feature of podocyte foot-process effacement and is associated with proteinuria. α-Actinin-4 in podocytes serves as a linker protein binding the actin filaments of the cytoskeleton.MethodsTo investigate the effect of ginseng total saponin (GTS) on the pathological changes of podocyte α-actinin-4 induced by diabetic conditions, we cultured mouse podocytes under normal glucose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Although the precise mechanisms of these deleterious effects have not been fully understood, derangement of the various SD and actin cytoskeleton molecules has been proposed as the common pathway leading to foot process effacement in podocytes [6,13]. In the present study, we newly demonstrated that IL-13 had a substantial impact on the redistribution and rearrangement of ZO-1, synaptopodin, α-actinin, previous and current studies [5,[20][21][22][23][24][25][26]. Recently, β-catenin has been shown to be involved in many pathological processes in podocytes [27].…”
Section: Discussionsupporting
confidence: 65%
“…Although the precise mechanisms of these deleterious effects have not been fully understood, derangement of the various SD and actin cytoskeleton molecules has been proposed as the common pathway leading to foot process effacement in podocytes [6,13]. In the present study, we newly demonstrated that IL-13 had a substantial impact on the redistribution and rearrangement of ZO-1, synaptopodin, α-actinin, previous and current studies [5,[20][21][22][23][24][25][26]. Recently, β-catenin has been shown to be involved in many pathological processes in podocytes [27].…”
Section: Discussionsupporting
confidence: 65%
“…Subsequently, the extracted saponin solution was dried at 50°C, before being mixed with 10 mL of methanol. Finally the saponin content was analyzed using HPLC (2690, Waters, USA) [14] , [15] .…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, podocyte cytoskeletal disarrangement can be attributed to intracellular α-Actinin-4 redistribution due to injury. In diabetes, for example, high glucose and advanced glycosylation end products (AGE) induced the inner cytoplasmic re-localization of α-Actinin-4 and disrupted actin fibers 41 .…”
Section: Discussionmentioning
confidence: 99%